THE EFFECT OF BRAND PRICE AND PRODUCT QUALITY ON SMARTPHONE PURCHASE DECISIONS AT KIRANA SMARTPHONE STORE - Mada, Yusuf Rayan; Sudarsono; Yahya, Siskawaty (LP2M Universitas Bina Mandiri Gorontalo, 2024)
This study aims to explore how factors such as price, brand, and product quality can influence smartphone purchasing decisions. The method used in this study is a quantitative method. This study conducted a survey with a sample of users or consumers who purchased smartphones at the Kirana Smartphone Store. Data were collected through a questionnaire that assessed consumer perceptions of price, brand, and product quality that influence smartphone purchasing decisions. The results of the study showed that price had a negative and significant effect on purchasing decisions. Based on the results of the t-test and significance value, it is known that the Price Variable (X1) is indicated by a calculated t-value of -3.499> t-table - 1.998 and a significance value of 0.001 <0.05. In addition, based on the results of the t-test and significance value, it is known that the Brand Variable (X2) is indicated by a calculated t value of 2.245> t-table 1.998 and a significance value of 0.002 <0.05. So it can be concluded that the brand variable has a positive and significant effect on purchasing decisions. Meanwhile, the product quality variable cannot influence consumer purchasing decisions. This is based on the results of the t-test and the significance value is known that the Product Quality Variable (X3) is indicated by a calculated t value of 0.689 < t-table 1.998 and a significance value of 0.000 > 0.05. Thus, the Product Quality variable is stated to have no influence on Purchasing Decisions.